2018
DOI: 10.1186/s12938-018-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

An extended OpenSim knee model for analysis of strains of connective tissues

Abstract: BackgroundOpenSim musculoskeletal models provide an accurate simulation environment that eases limitations of in vivo and in vitro studies. In this work, a biomechanical knee model was formulated with femoral articular cartilages and menisci along with 25 connective tissue bundles representing ligaments and capsules. The strain patterns of the connective tissues in the presence of femoral articular cartilage and menisci in the OpenSim knee model was probed in a first of its kind study.MethodsThe effect of knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 42 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…According to the quality assessment results presented in Table 2 , several articles had limited modelling technique descriptions [ 15 , 16 , 19 , 20 , 27 , 33 ] and validation methods [ 16 , 18 , 25 , 27 , 35 , 37 , 38 ]. In 12 of the selected studies [ 14 17 , 20 , 24 27 , 31 , 37 , 38 ], the sensitivity of the model outputs on ligament model parameters has not been assessed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the quality assessment results presented in Table 2 , several articles had limited modelling technique descriptions [ 15 , 16 , 19 , 20 , 27 , 33 ] and validation methods [ 16 , 18 , 25 , 27 , 35 , 37 , 38 ]. In 12 of the selected studies [ 14 17 , 20 , 24 27 , 31 , 37 , 38 ], the sensitivity of the model outputs on ligament model parameters has not been assessed.…”
Section: Resultsmentioning
confidence: 99%
“…A range of musculoskeletal modelling software packages has been used across the selected studies ( Fig 2A and Table 3 ). 14 studies [ 15 17 , 20 25 , 27 , 29 , 32 , 34 , 35 ] used OpenSim [ 39 ], four studies [ 18 , 36 38 ] used SIMM [ 40 ], two studies [ 26 , 28 ] used AnyBody Modelling System (AnyBody Technology, Aalborg, Denmark), one study [ 30 ] used ADAMS [ 41 ], one study [ 14 ] used SimWise-4D platform (Design Simulation Technologies, DST, Canton, MI, USA), one study [ 19 ] used KneeSIM (LifeModeler Inc., San Clemente, CA), one study [ 33 ] used Musculoskeletal Joint Modeler [ 42 ], and one study [ 31 ] used Working Model 3D (Working Model 3D, MSC, Software Corp., Santa Ana, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies, using XROMM to capture detailed kinematics of passerines should ensure that at least one of the long bones includes at least 3 markers to reduce the reliance on the user during scientific rotoscoping. The simulations here included IER motion of the knee and ankle joints, however the active muscle actuation of these degrees of freedom was not considered in line with previous studies and under the assumption that typically small moments are balanced by passive structures such as ligaments [37,55]. Previous studies reported the take-off velocity of the zebra finch to be around 1.7m/s [2,6] which is faster than the take-off velocity, measured here from the XROMM data which ranged between 1.08-1.39 m/s.…”
Section: Discussionmentioning
confidence: 99%